Conscious business : how to build value through values - Kofman, Fred, ....-; Senge, Peter, ....-; Wilber, Ken, ....- (Boulder (Colo.) : Sounds True, 2013)
Consciousness is the main source of organizational greatness. Conscious business, explains Fred Kofman, means finding your passion and expressing your essential values through your work. A conscious business seeks to promote the intelligent pursuit of happiness in all its stakeholders. It produces sustainable, exceptional performance through the solidarity of its community and the dignity of each member.